2014
DOI: 10.1186/1471-2334-14-341
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of children who died from hand, foot and mouth disease in Vietnam, 2011

Abstract: BackgroundIn 2011, a large outbreak of hand, foot and mouth disease (HFMD) in Vietnam resulted in 113,121 children seeking medical attention, of whom170 died. Understanding the epidemiology of fatal HFMD may improve treatment and help targeting prevention activities for vulnerable populations. We describe epidemiological and clinical characteristics of children who died from HFMD in Vietnam in 2011.MethodsClinical data were obtained through reviewing medical records of the deaths occurring from January through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 15 publications
3
62
1
3
Order By: Relevance
“…We also found that more boys were affected by HFMD than girls, and the gender distribution was similar to that observed in other Asian regions [29, 30]. This may indicate that boys are more susceptible to enterovirus infection.…”
Section: Discussionsupporting
confidence: 87%
“…We also found that more boys were affected by HFMD than girls, and the gender distribution was similar to that observed in other Asian regions [29, 30]. This may indicate that boys are more susceptible to enterovirus infection.…”
Section: Discussionsupporting
confidence: 87%
“…The CFR in Cambodia was extremely high compared with that observed in other countries such as in China, Taiwan and Vietnam, where the CFR ranged from 0.14% to 34% depending on year, age group and gender. 52, 64, 65 Subgenotype C4a, which was detected in most Cambodian cases, was already suspected to both cause more severe disease (CPF) and be associated with higher lethality. 50, 52, 66, 67, 68 We did not find any significant molecular difference, however, between EV-A71 subgenotype C4a sequences isolated from mild HFMD and severe (CNSI and CPF) cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, this relationship is less clear for tropical and subtropical Asia. The extracted data on Southwest China, 15,21 South China, 2,15,22,23 Hong Kong 24,25 and Taiwan [26][27][28] show that outbreaks typically happen in late spring and fall. No distinct pattern is obvious for tropical regions as seen from data in Thailand, [29][30][31] Vietnam, 32,33 Malaysia 34 and Singapore, [35][36][37][38] where outbreaks occur sporadically throughout the year, although models have been developed for Singapore (≈1° north) that show a positive statistical relationship between maximum daily temperature above 32°C with HFMD incidence in the subsequent 1-2 weeks.…”
Section: Timing and Seasonality Of Hfmd Outbreaksmentioning
confidence: 99%